Hubungan Intensitas Penggunaan Media Sosial dengan Kualitas Tidur pada Siswa SMA Negeri 1 Denpasar - I Putu Rama Crishna Febyantara; Putu Asih Primatanti; I Gde Yudhi Kurniawan (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Humans have two main needs, namely physiological and psychological needs. Physiological needs include eating, drinking and sleeping which are important for health and well-being. Sleep quality can be disturbed by excessive use of social media, especially in adolescents. To explore the relationship between the intensity of social media use and sleep quality, a study was conducted on students of SMA Negeri 1 Denpasar. This study involved 381 respondents, using a cross-sectional study design with data collection using the PSQI questionnaire to evaluate sleep quality and a questionnaire on the intensity of social media use. The results showed that most of the respondents were 16 years old (30.7%) and the average age was 16.5 years. The sex of the most respondents was female with a total of 207 people (54.3%). Most of the respondents with low intensity of using social media were 191 people (50.1%) and respondents with high intensity were 190 people (49.9%). The majority of respondents had poor sleep quality as many as 240 people (63.0%) and the rest had good sleep quality as many as 141 people (37.0%). The conclusion in this study is that there is no relationship between the intensity of social media use and the quality of sleep in students of SMA Negeri 1 Denpasar (p=0.157) which may be caused by the influence of other factors not examined in this study.